2017
DOI: 10.1016/j.conbuildmat.2016.12.190
|View full text |Cite
|
Sign up to set email alerts
|

New methodology to estimate the fatigue behavior of bituminous mixtures using a strain sweep test

Abstract: Fatigue cracking of bituminous mixtures is closely related to the loss of ductility produced by the stiffening of the bituminous binder. The main two factors that cause the asphalt binder to lose its ductility are aging and exposure to low temperatures. However, most of the tests designed to evaluate the fatigue behavior of bituminous mixtures are very time consuming, and make unpractical those studies that try to evaluate the influence of many variables. In this research project a strain sweep test was used t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…A review of the existing literature indicated that research into the stability of riparian revetment adopting vegetated bituminous mixtures is mostly limited to static loading conditions [ 23 , 24 , 25 , 26 , 27 ]. Existing review-based studies [ 28 ] have not sufficiently addressed the dynamic features of bituminous mixtures, especially under cyclic loading [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…A review of the existing literature indicated that research into the stability of riparian revetment adopting vegetated bituminous mixtures is mostly limited to static loading conditions [ 23 , 24 , 25 , 26 , 27 ]. Existing review-based studies [ 28 ] have not sufficiently addressed the dynamic features of bituminous mixtures, especially under cyclic loading [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…It provides the maximum strain amplitude the material can sustain without permanent change to its properties, and the maximum strain amplitude it can endure under cyclic conditions before failing completely. These two strain values may be used to sketch an approximation of the fatigue law of the material [22]. The fatigue laws obtained through this procedure were compared with those obtained by applying the classical method based on time sweep tests, showing a good agreement between them [23,24].…”
Section: Introductionmentioning
confidence: 99%